DEVELOPING ENGLISH LEARNING MATERIAL OF FRONT OFFICE FOR 11TH GRADE STUDENTS VOCATIONAL HIGH SCHOOL OF TOURISM MAJOR AT SMKN 2 SINGARAJA - Arta Yani, Ni Kadek; Wedanti, Ni Wedhanti Nyoman Karina; yana, Gede Mahendra (Universitas Suryakancana, 2023)
This study aimed at developing English learning materials for the front office of 11th grade students. ESP-based goals in teaching English were mastery of English language skills specifically for students in the field of study following the program of study chosen by the students previously. This study employed the D&D model proposed by Richey and Klein (2014) with the ADDE steps. The subjects of this study were front office teachers and students of 11th grade, especially in class XI AP 5 conducted at SMKN 2 Singaraja and the object of this study was the English materials of the front office. Interviews with teachers, administrating questionnaires, and document analysis were used to collect the data. The data were analyzed qualitatively and quantitatively. The results of the study showed that the English Learning Material of Front Office for 11th Grade Students Vocational High School of Tourism Major at SMKN 2 Singaraja was categorized as